Big Data Analytic: Challenges & Solutions - Bahrami, Ahmad Zia (Journal of Natural Sciences – Kabul University, 2021)
In today's Big Data era, data is generated and collected rapidly, in large volumes, and in various formats from diverse sources. Many governments and private organizations view the Big Data era as an opportunity to compete and thrive. By utilizing Big Data analytic techniques, they have gained valuable knowledge and insights from massive datasets, which they use in decision-making and planning processes. Big Data analytics differs from traditional data analytics due to its volume, variety, and velocity. However, numerous challenges exist in this field. This article explores the fundamental concepts of Big Data analytics, examines its problems and challenges, and proposes suitable solutions to address them.